The Effect of Online-Based Relational Marketing Strategy on Service Value and Student Trust at University - Jajang Sugiat (AL-ISHLAH: Jurnal Pendidikan, 2023)
Student trust has a vital role in college success and increases when the value of the services offered has a high quality, forming an image. Moreover, a competitive academic environment becomes important to create a value formation process. This study analyzes the relational marketing strategy, service value, and student trust through an explanatory survey method. Furthermore, it determines the effect of relational marketing strategy on service value and student trust in private colleges in West Java, Indonesia. The data were collected from 391 respondents through a questionnaire. The first part of the questionnaire aimed to collect data related to the respondents' demographic characteristics, such as gender, address, and reasons for selecting a college. Data analysis was conducted using path techniques to explain the relationship and influence between manifest and confirmatory variables. The results showed that the relational marketing strategy and service value are in a good and fairly good category. Meanwhile, student trust is in the fairly good category, and the relational marketing strategy has a significant effect on service value at private colleges in West Java. The conclusion and implications of this study are that the relational marketing strategy has a positive and significant effect on service value. In this technique, the qualities of empathy and dependability are more prominent. Apart from that, the honesty, sincerity, and commitment of higher education institutions in increasing the value of services with the care and friendliness of lecturers and education staff are also appropriate according to students.